Case Report: Uniportal robot-assisted thoracoscopic double-sleeve lobectomy after neoadjuvant immunotherapy - Fang, Ziyao; Li, Chang; Bosinceanu, Mugurel L.; Ding, Cheng; Zhao, Jun; Gonzalez-Rivas, Diego (Frontiers in Surgery, 2024)
Minimally invasive thoracic surgery including video-assisted thoracoscopic surgery and robot-assisted thoracoscopic surgery has been proven to advantage over open thoracotomy with less pain, fewer postoperative complications, faster discharge and better tolerated among elderly patients. We introduce a uniportal robotic-assisted thoracoscopic double sleeve lobectomy performed on a patient following neoadjuvant immunotherapy. Specialized instruments like customized trocars with a reduced diameter, bulldog clamps and double needle sutures were utilized to facilitate the maneuverability through the single incision. This technique integrates the merits of multiport robotic assisted thoracic surgery with uniportal video-assisted thoracoscopic surgery.